PERAN PEKERJA SOSIAL DALAM PEMBINAAN REMAJA DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI PEKANBARU - Yani, Fitri; Wilson, Wilson; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe the role of social workers in the development of adolescents (children dealing with the law of the category of children as perpetrators of crime) in social institutions of youth development (Psbr) Rumbai Pekanbaru. This research uses qualitative research with descriptive approach. The subjects of the study were young social worker, first pekso candidate and psychological child protection center. Data collection through observation techniques, interviews and documentation. The number of child offenders from January to May 22, 2018 amounted to 20 children with different cases. The interview guide contains 54 questions about the role of social workers in child coaching, with a subfocus of facilitators, brokers, mediators, defenders and patron with each sub-indicator 3-4. The results show that the role of social workers in the development of adolescents in youth social institutions (Psbr) Rumbai Pekanbaru includes: the role of social workers in the guidance of child offenders shows that the role of social workers play an active role in guidance as facilitators, intermediaries, mediators, defenders and patrons. As well as friends and parents both, coaching can also help solve a teenage case and may affect a child's behavior. In the guidance of children obtaining education in the form of vukational training, spiritual guidance, physical guidance, social and psychosocial useful when children out of the house between (LPKS). Closing children will make it difficult for social workers to solve child cases. The security and confidentiality of adolescent identity is a form of protection services provided. Keywords: The Role of Social Workers, Children in Conflict With Law (Children as Criminal Offenders.